Assessing allocation of responsibility for health management in pediatric liver transplant recipients. (31st March 2015) - Bilhartz, Jacob L.; Lopez, M. James; Magee, John C.; Shieck, Victoria L.; Eder, Sally J.; Fredericks, Emily M.
Abstract Given the increased risk for non‐adherence and poor health outcomes in late adolescence, there is a need for better methods to evaluate and improve the transition process as adolescent patients are prepared to be independent adults. This study assessed the psychometrics and concurrent validity of a newly developed measure of AoR for health management in pediatric liver transplant patients. A total of 48 patients and 37 parents completed a 13‐item measure of AoR. We performed an exploratory PCA on survey results and used component scores to assess the relationship between AoR and age, age at transplant, adherence, and health outcomes. Two primary components were identified: communication with the healthcare system and self‐management tasks. Parent perception of adolescent responsibility for tasks related to communicating with the healthcare system was correlated, in younger patients, with increased non‐adherence while responsibility for tasks related to self‐management was correlated, in older patients, with decreased non‐adherence. These results support AoR as a two‐domain construct, and they provide targets for monitoring and intervention as adolescent patients advance toward transfer.